2012
DOI: 10.1029/2012gc004260
|View full text |Cite
|
Sign up to set email alerts
|

Heat flow in the Lesser Antilles island arc and adjacent back arc Grenada basin

Abstract: [1] Using temperature gradients measured in 10 holes at 6 sites, we generate the first high fidelity heat flow measurements from Integrated Ocean Drilling Program drill holes across the northern and central Lesser Antilles arc and back arc Grenada basin. The implied heat flow, after correcting for bathymetry and sedimentation effects, ranges from about 0.1 W/m 2 on the crest of the arc, midway between the volcanic islands of Montserrat and Guadeloupe, to <0.07 W/m 2 at distances >15 km from the crest in the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 138 publications
(183 reference statements)
6
44
0
Order By: Relevance
“…This anomaly is well correlated with a doming of the CPD beneath the active arc. The deepening of the CPD in front of the subduction trench is consistent with the relatively low thermal gradient evidenced by Manga et al [2012], commonly reported in similar contexts [Schubert and Peter, 1974]. Even at our scale, these evidences support CPD variations (or 580°C isotherm depth variations) as a witness of differences in thermal structure at the lithospheric scale.…”
Section: Comparison Of Cpd With Heat Flow Measurementssupporting
confidence: 68%
See 3 more Smart Citations
“…This anomaly is well correlated with a doming of the CPD beneath the active arc. The deepening of the CPD in front of the subduction trench is consistent with the relatively low thermal gradient evidenced by Manga et al [2012], commonly reported in similar contexts [Schubert and Peter, 1974]. Even at our scale, these evidences support CPD variations (or 580°C isotherm depth variations) as a witness of differences in thermal structure at the lithospheric scale.…”
Section: Comparison Of Cpd With Heat Flow Measurementssupporting
confidence: 68%
“…At first order correlation can be observed between our CPD results and the measurements from Manga et al [2012]. According to Manga et al [2012], a main high heat flow anomaly corresponds to the active arc and fore-arc domain (~0.08 W/m 2 ). We have to remember that high heat flow values are commonly attributed to volcanic and metamorphic regions (high thermal conductivities).…”
Section: Comparison Of Cpd With Heat Flow Measurementssupporting
confidence: 54%
See 2 more Smart Citations
“…Using measured thermal conductivity, the implied heat flow is 59 ± 5 mW/m 2 . This estimate does not need a correction for bathymetry, and sedimentation lowers the measured near-surface heat flow by as much as 4% (Manga et al, 2012). Of all the sites, this is the only one where a quadratic fit to the data (rather than a linear fit) produces a quadratic term that is statistically significant; however, modeling of this data indicates that a linear fit is still favored (Manga et al, 2012).…”
Section: Downhole Temperature Measurementsmentioning
confidence: 92%